Digital Financial Literacy, Consumptive Behavior, and Behavioral Intention in Using SPayLater in Indonesia - Cristina Cristina; Fry Melda Saragih (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The rapid growth of financial technology (fintech) is reshaping how consumers manage their finances, particularly through e-commerce platforms such as Shopee. Among its innovations, the SPayLater feature has gained wide attention but also raised concerns about impulsive spending and low digital financial literacy among consumers. This study investigates the influence of digital financial literacy and consumptive behavior on consumers’ decisions to use SPayLater, while also testing the mediating role of behavioral intention. A quantitative survey was conducted with 100 SPayLater consumers using a structured questionnaire, and the data were analyzed through multiple linear regression and path analysis. The findings show that both digital financial literacy and consumptive behavior significantly affect consumers’ decisions, whereas behavioral intention does not have a direct effect but partially mediates the relationship between consumptive behavior and usage decisions. These results highlight the importance of strengthening consumers’ digital financial literacy and managing consumptive behavior to encourage wiser and more responsible use of fintech services.